INNOVATIVE APPROACHES TO PERSONNEL MANAGEMENT IN THE CONDITIONS OF DIGITALIZATION OF ENTERPRISES - RUDENKO, Mykola; LAKUTIN, Dimirii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines innovative approaches to personnel management in the context of the digitalization of enterprises.The level of possession of digital skills of the population of Ukraine had positive dynamics during the years of research. However, this is not happening as rapidly as the world's digital technologies are developing, so the number of people with primitive knowledge is high (almost half of the respondents), which does not allow them to fully use digital technologies and apply them in the process of work and education. The authors highlighted the most in-demand employees' skills, dividing them into three main blocks - technical, informational, and communication, making it possible to comprehensively describe the list of requirements for competencies and skills of search results with the application of a practical assessment of employment opportunities.Described modern methods of personnel selection and the expediency of their application by domestic enterprises and proposed using different personnel selection ways depending on the size of domestic enterprises (large, medium, and small). New advanced methods of personnel evaluation, that allow determining the level of skills of employees as quickly and efficiently as possible were considered and should be used depending on the goal pursued by the enterprise during personnel assessment because such methods focus on competencies, mainly for the performance of tasks set by job duties.The latest professional training methods of personnel were analyzed using two groups of directions - on-the-job and off-the-job (training at the workplace or outside of it using digital technologies). Described methods of personnel training in the conditions of digitalization are perspective for domestic enterprises and showed high efficiency in their practical application process. Therefore, the authors recommend these methods for implementation to comprehensively develop the skills of employees of enterprises under current operating conditions.
Keywords: innovative approaches; personnel; management; digitalization of enterprises; employee skills; selection methods; personnel evaluation; training